Gender Disparities in Climate Resilience: Amplifying Voices of Women in Climate Change Issue in Indonesia’s Chairmanship of ASEAN 2023 - Anggraheni, Palupi; Hanura, Marten; Subhan, Muhammad; Setyaningsih, Dewi; Diaz, Yohana Grezia (Jurnal Ilmiah Hubungan Internasional, 2024)
Indonesia officially received the mandate as Chair of ASEAN from January 1 to December 31, 2023.  During the post-COVID-19 pandemic, in the period 2022-2023 Indonesia received appreciation from the  international community regarding the successful organization of international forums including the G-20.  Indonesia's attitude is considered to remain neutral and maximize Indonesia's function as a middle-power at the  level of multilateralism, amid geopolitical conflicts such as the Ukraine-Russia conflict and regional instability in  the Middle East. But on the other hand, there are other issues in the realm of low politics, including the issue of  climate change and women's vulnerability. As a region with a long coastline, it has a high potential risk as a chain  effect of climate change. In addition, the gender disparity that is still quite high in this region is one of the factors  that make women vulnerable to climate change issues, such as vulnerability in the labor, health and gender-based  violence sectors. This paper focuses on seeing the extent to which Indonesia's role as chair of ASEAN in 2023  advocates the issue of climate change in a gender framework. The concept of Gender Equality and Social Inclusion  (GESI) which focuses on women's participation in the public sector and policy initiation is used as a framework.  The expected results of this study can show the relationship between environmental issues and women's  vulnerability and the imbalance between women's participation in the public sector and policy initiation.  Keywords: GESI, women, climate change, ASEAN Chairmanship, Indonesia.